Multifunctional Superabsorbent Polymer under Residue Incorporation Increased Maize Productivity through Improving Sandy Soil Properties. (13th December 2022) - Li, Rong; Hou, Xianqing; Li, Peifu; Wang, Xi'na
Abstract : Superabsorbent polymer (SAP) is a new water-retaining and nutrient-holding material with the potential to improve soil properties and promote crop growth in arid and semiarid areas. This study investigated the effects of multifunctional SAP on the sandy soil properties and maize productivity in Yanghuang irrigated area of Ningxia where residue incorporation was a common agricultural practice, we tested multifunctional SAP at different doses of 0, 30, 60, 90, and 120 kg ha –1 under the residue incorporation to the field. The soil bulk density in the 0–0.40 m layer was significantly lower by 6.2–8.2% under SAP at 60–120 kg ha –1 compared with no SAP, but the total soil porosity was improved significantly by 8.5–11.2%, where the SAP at 90 and 120 kg ha –1 had the greatest effects. The applications of SAP at 60 and 90 kg ha –1 significantly improved soil organic matter, and available P and K contents in the 0–0.40 m soil layer. The soil water storage (0–1.0 m) under SAP at 60–120 kg ha –1 was significantly increased by 17.1–18.7% compared with no SAP throughout the whole maize growing season. The SAP at 60–90 kg ha –1 significantly promoted crop growth and maize yield formation, and increased grain yield, whereas the net income were the highest with applying SAP at 30–60 kg ha –1 . In combination with the soil physicochemical property, crop productivity and economic benefit comprehensive analysis of this two-year study, we recommended that the application of multifunctional SAP at 30–60 kg ha –1 under residue incorporation significantly improved the sandy soil properties, as well as increasing maize growth, crop productivity, and obtain the higher net income for farmers in Yanghuang irrigation area of Ningxia, China.